2008
DOI: 10.1086/590949
|View full text |Cite
|
Sign up to set email alerts
|

ChandraObservations of the Pulsar B1929+10 and Its Environment

Abstract: We report on two Chandra observations of the 3 Myr old pulsar B1929+10, which reveal a faint compact ($9 00 ; 5 00 ) nebula elongated in the direction perpendicular to the pulsar's proper motion, two patchy wings, and a possible short ($3 00 ) jet emerging from the pulsar. In addition, we detect a tail extending up to at least 4 0 in the direction opposite to the pulsar's proper motion, aligned with the $15 0 long tail detected in ROSAT and XMM-Newton observations. The overall morphology of the nebula suggests… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 50 publications
5
30
0
Order By: Relevance
“…PSR B0943+10 is thus similar to other old and middle aged pulsars from which thermal X-rays from a small emitting area have been detected (e.g. [34,35,36,37]). It is believed that the surface heating in these pulsars results from the flow of backward-accelerated particles produced in the star magnetosphere above the polar caps [32,38].…”
Section: The Pulsed Thermal Componentsupporting
confidence: 66%
“…PSR B0943+10 is thus similar to other old and middle aged pulsars from which thermal X-rays from a small emitting area have been detected (e.g. [34,35,36,37]). It is believed that the surface heating in these pulsars results from the flow of backward-accelerated particles produced in the star magnetosphere above the polar caps [32,38].…”
Section: The Pulsed Thermal Componentsupporting
confidence: 66%
“…Old pulsars with their spectrum dominated by hot spot radiation show that an actual polar cap is considerably smaller than R dp , see e.g. PSR J0108−1431 (Pavlov et al 2009;Posselt et al 2012), PSR J0633+1746 (Kargaltsev et al 2005), PSR B1929+10 (Misanovic, Pavlov & Garmire 2008). Furthermore, the estimated magnetic field strengths at the polar cap for these pulsars (Bs ∼ 10 14 G) and temperatures of a few million Kelvin satisfy the condition for the formation of a Partially Screened Gap (PSG) (see Gil et al 2003;Medin & Lai 2007).…”
Section: Conditions At the Inner Acceleration Regionmentioning
confidence: 99%
“…There have been many attempts to measure the polar‐cap blackbody temperature and source area of a subset of radio pulsars. We refer to Zavlin & Pavlov (2004) for B0950+08, De Luca et al (2005) for B0656+14 and B105552, Tepedelenlioğlu & Ögelman (2005) for B062828, Zhang, Sanwal & Pavlov (2005) for B0943+10, Kargaltsev, Pavlov & Garmire (2006) for B1133+16, Gil et al (2008) for B0834+06 and Misanovic, Pavlov & Garmire (2008) for B1929+10. Five pulsars (B062828, B0834+06, B0943+10, B1133+16, B1929+10) have source areas one or two orders of magnitude smaller than the canonical area, but unfortunately, a systematic comparison with equations ()–(42) is not possible because in most instances the authors are able to say only that the observed X‐ray spectrum is consistent with the stated temperature and source area.…”
Section: Nulls Subpulse Drift and Polar‐cap Coherencementioning
confidence: 99%